1981
DOI: 10.1159/000459198
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Activity of Serum Alkaline Phosphatase

Abstract: This paper reports a seasonal variation in alkaline phosphatase (ALP) levels in the serum, with low values occurring in summer and high in winter. These variations were found both in indoor and outdoor workers and in a group of elderly women in a long-stay ward. The seasonal change in ALP was in the opposite direction to the seasonal change in the serum levels of 25-hydroxyvitamin D. No such change was seen in the serum levels of gamma- glutamyltransferase. It is suggested that the seasonal change in plasma AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Craft, equipment, machine operating, and assembling workers2812South Korea (33° - 38°N)Cross-sectional<50 nmol/L: 61.6%2. Skilled agricultural, forestry, and fishery workers2572<50 nmol/L: 38.5%Bacchel (2015) [27]Farmers6North-West Punjab, India (31°15′N)Cross-sectional<75 nmol/L: 50%<25 nmol/L: 50%Indoor WorkersDevgun (1981) [85]Laboratory staff8Dundee, Scotland (56°30′N)Descriptive43.9 ± 17.0Devgun (1981) [25]Indoor workers9Scotland (56°30′N)Descriptive42.9 ± 15.3Maeda (2007) [108]Plant and office workers28Sao Paulo, Brazil (23° 34′S)Descriptive94.0 ± 32.6Gulvady (2007) [109]Senior executives75Mumbai, India (19°08′ N)Descriptive<50 nmol/L: 83%Islam (2008) [110]Garment factory workers200Dhaka, Bangledesh (23°81′N)Descriptive36.7 ± 11.2<50 nmol/L: 86.5%Azizi (2009) [104]Industry, civil service, etc.104Israel, Beer Sheva (31°25′ N)Interventional57.5 ± 20.8Itoh (2011) [28]Indoor daytime workers4Kawasaki City, Japan (35°53′N)Interrupted time series49.7 ± 7.9Vu (2011) [111]Office workers213Brisbane, Australia (27°S)Descriptive62.2 ± 22.5<75 nmol/L: 43.3%<50 nmol/L: 42.5%Choi (2011) [106]1. Administration, clerical work1047Cross-sectional45.8 ± 16.5<75 nmol/L: 93.4%<50 nmol/L: 87.1%53.8 ± 18.5<75 nmol/L: 87.1%<50 nmol/L: 50%2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Craft, equipment, machine operating, and assembling workers2812South Korea (33° - 38°N)Cross-sectional<50 nmol/L: 61.6%2. Skilled agricultural, forestry, and fishery workers2572<50 nmol/L: 38.5%Bacchel (2015) [27]Farmers6North-West Punjab, India (31°15′N)Cross-sectional<75 nmol/L: 50%<25 nmol/L: 50%Indoor WorkersDevgun (1981) [85]Laboratory staff8Dundee, Scotland (56°30′N)Descriptive43.9 ± 17.0Devgun (1981) [25]Indoor workers9Scotland (56°30′N)Descriptive42.9 ± 15.3Maeda (2007) [108]Plant and office workers28Sao Paulo, Brazil (23° 34′S)Descriptive94.0 ± 32.6Gulvady (2007) [109]Senior executives75Mumbai, India (19°08′ N)Descriptive<50 nmol/L: 83%Islam (2008) [110]Garment factory workers200Dhaka, Bangledesh (23°81′N)Descriptive36.7 ± 11.2<50 nmol/L: 86.5%Azizi (2009) [104]Industry, civil service, etc.104Israel, Beer Sheva (31°25′ N)Interventional57.5 ± 20.8Itoh (2011) [28]Indoor daytime workers4Kawasaki City, Japan (35°53′N)Interrupted time series49.7 ± 7.9Vu (2011) [111]Office workers213Brisbane, Australia (27°S)Descriptive62.2 ± 22.5<75 nmol/L: 43.3%<50 nmol/L: 42.5%Choi (2011) [106]1. Administration, clerical work1047Cross-sectional45.8 ± 16.5<75 nmol/L: 93.4%<50 nmol/L: 87.1%53.8 ± 18.5<75 nmol/L: 87.1%<50 nmol/L: 50%2.…”
Section: Resultsmentioning
confidence: 99%
“…Serum 25-(OH)D levels vary widely according to the season of the year in which the studies or collection of samples are conducted [25, 85], thus establishing season of the year as a confounder of serum vitamin D level [84]. Several lines of evidence suggest that there is a high variability in seasonal vitamin D levels across the globe [86, 87].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in the serum BAP concentration in all groups was most likely a result of winter elevation of enzyme secretion. Seasonal variation of alkaline phosphatase activity has been reported previously (Devgun et al ., ; Douglas et al ., ). It should be noted that BAP mass concentration (not activity) was measured in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Osteocalcin may be elevated in the winter and spring and total and bone alkaline phosphatase may be decreased in the winter and spring [185,186]. However, other studies, including a large cross-sectional study of subjects aged 50±80 years, has shown that the rhythms of osteocalcin and bone alkaline phosphatase coincide [63,187]. The differences between the ®ndings of these studies may be due some of them being longitudinal and the others being crosssectional.…”
Section: Seasonalmentioning
confidence: 99%